2020
DOI: 10.3390/jcm9040903
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Patients with Catecholaminergic Polymorphic Ventricular Arrhythmia

Abstract: Background: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare inherited disorder causing life-threatening arrhythmias. Long-term outcome studies of the channelopathy are limited. Objective: The aim of the present study was to summarize our knowledge on CPVT patients, including the clinical profile treatment approach and long-term outcome. Methods: In this single center study, we retrospectively and prospectively collected data from nine CPVT patients and analyzed them. Results: We reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…The subcutaneous implantable cardioverter-defibrillator (S-ICD) is an established therapy for the prevention of sudden cardiac death (SCD) ( 1 ) and an alternative to a transvenous implantable cardioverter-defibrillator (T-ICD) system in selected patients ( 2 ). S-ICD may be particularly useful in patients with channelopathies ( 3 ) since several studies showed a high complication rate in those implanted with T-ICD ( 4 6 ). S-ICD is non-inferior to T-ICD concerning device-related complications or inappropriate shocks in patients with an indication for defibrillator therapy and not in need of pacing ( 7 12 ); however, these data are limited to short follow-up observational case-control studies ( 7 10 ) or the context of the randomized clinical trial ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The subcutaneous implantable cardioverter-defibrillator (S-ICD) is an established therapy for the prevention of sudden cardiac death (SCD) ( 1 ) and an alternative to a transvenous implantable cardioverter-defibrillator (T-ICD) system in selected patients ( 2 ). S-ICD may be particularly useful in patients with channelopathies ( 3 ) since several studies showed a high complication rate in those implanted with T-ICD ( 4 6 ). S-ICD is non-inferior to T-ICD concerning device-related complications or inappropriate shocks in patients with an indication for defibrillator therapy and not in need of pacing ( 7 12 ); however, these data are limited to short follow-up observational case-control studies ( 7 10 ) or the context of the randomized clinical trial ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Так, A. Mazzanti и соавт., изучив результаты лечения 216 больных с КПЖТ, показали, что в течение (в среднем) 9 лет жизнеугрожающие события развились у 13% больных, получающих лечение только бета-адреноблокаторами [14]. В другом исследовании на примере 9 пациентов с КПЖТ со средним периодом наблюдения 8,6 года было установлено, что на фоне базовой терапии бета-адреноблокаторами аритмогенные события возникли у трех пациентов [15]. Недостаточная эффективность бета-адреноблокаторов при КПЖТ отмечена также и в работе S.G Priori и соавт., согласно результатам которой имплантация кардиовертера-дефибриллятора (ИКД) потребовалась 30% таких больных [16].…”
Section: бета-адреноблокаторыunclassified
“…Betablockers, sedation as well as flecainide have been The different steps of the first phase are summarized. implemented for patients with catecholaminergic polymorphic ventricular tachycardia (38)(39)(40).…”
Section: Phase 3: Anti-arrhythmic Therapies 41 Conversion To Sinus Rh...mentioning
confidence: 99%